Criptococosis meníngea en personas que viven con VIH : Serie de casos en un hospital regional argentino (SigMe, 2023)
Meningeal cryptococcosis is an opportunistic infection that affects people with human immunodeficiency virus (PLHIV) with a high level of immunosuppression. It is associated with high morbidity and mortality. Due to the lack of official epidemiological data in Argentina and a limited number of published regional studies, the present paper aims to describe the main clinical-biochemical characteristics, therapeutic management and evolution of a group of PLHIV with meningeal cryptococcosis in a referral hospital of the north-central region of the province of Santa Fe (Argentina). 10 patients were included, aged 44 (61-34) years and a mean of 3 (30-0) years of evolution of the HIV infection. When making the first consultation, they presented 15 (40-2) days of evolution, being fever the most common symptom. All of them received treatment with liposomal amphotericin B for 26.5 (44-2) days. Cerebrospinal fluid (CSF) culture control 14 days after starting therapy was positive in 5 individuals. Five subjects evolved favorably with hospital discharge and outpatient follow-up, while five required attention in the Intensive Care Unit for mechanical respiratory assistance. Five of the PLHIV included died.
Keywords: Cryptococcus; Opportunistic infections related to AIDS; Meningeal cryptococcosis; criptococosis